DIPLOMASI KESEHATAN GLOBAL INDONESIA DALAM MENCIPTAKAN KEAMANAN KESEHATAN DI INDONESIA MELALUI COVAX FACILITY (2020-2021) - Prameswari Chitra Dewi (2022)
Covid-19 is a health problem that emerged at the end of 2019, which originated in China. The research will discuss Indonesia's global health diplomacy in obtaining the Covid-19 vaccine through the Covax Facility, which aims to create health security. The concepts and theories used are global health diplomacy, and health security. The research method uses descriptive qualitative research, with the aim of researching Indonesia's efforts to obtain a Covid-19 vaccine through global health diplomacy to achieve the national interest in protecting. Researchers use internet-based research as data collection techniques, and this study uses primary and secondary data sources. In addition, using data collection techniques from the book "Qualitative data analysis: An expand sourcebook (2nd ed.)" by A.Michael Huberman in 2014 which describes the flow of data analysis consisting of data collection, data condensation, data display, drawing conclusions and verification. The Covid-19 health problem which requires effective and appropriate handling, through the Covid-19 vaccination which has become a global effort and Indonesia implements it for the community to form herd immunity to reduce the negative impact of Covid-19 which disrupts health and causes death. Indonesia to obtain a Covid-19 vaccine through global health diplomacy at the multilateral level with the Covax Facility. Joining the Covax Facility, Indonesia gets the proceeds for the procurement of the Covid-19 vaccine. In addition, there is Indonesia's role in the Covax Facility through the Covax AMC for the Minister of Foreign Affairs Retno Marsudi who supports the discovery of the Covid-19 vaccine for each country. Global health diplomacy is the main and important thing to build communication to create security from the dangers of Covid-19. In the situation of the global Covid-19 pandemic, it can be said that countries cannot get out of health problems themselves, but need international cooperation.